Comments on 'the age of fossil stw573 ('little foot'): An alternative interpretation of 26al/10be burial data'. - Stratford, D.; Granger, D.E.; Bruxelles, L.; Clarke, R.J.; Kuman, K.; Gibbon, R.J. (Academy of Science of South Africa (ASSAf), 2017)
No abstract available.
Keywords: Sterkfontein; Australopithecus; Stratigraphy; Depositional age; Taphonomy